2009
DOI: 10.4103/0255-0857.53199
|View full text |Cite
|
Sign up to set email alerts
|

Aids-Associated Parasitic Diarrhoea

Abstract: Since the advent of human immunodeficiency virus infection, with its profound and progressive effect on the cellular immune system, a group of human opportunistic pathogens has come into prominence. Opportunistic parasitic infection can cause severe morbidity and mortality. Because many of these infections are treatable, an early and accurate diagnosis is important. This can be accomplished by a variety of methods such as direct demonstration of parasites and by serological tests to detect antigen and/or speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
4

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 7 publications
0
28
0
4
Order By: Relevance
“…Study of HIV-infected patients showed that eosinophilia was strongly associated with isosporiasis; however higher eosinophil counts were described in I. belli infected patients without weight loss (Certad et al 2003). This finding could be described that in patients with considerable weight loss the HIV disease is more severe and defect of the immune system may involve the production of eosinophils (Arora and Arora 2009). Celiac was not confirmed in our patient, however celiac disease is one of the most frequent causes of malabsorption as reported previously (Behera et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Study of HIV-infected patients showed that eosinophilia was strongly associated with isosporiasis; however higher eosinophil counts were described in I. belli infected patients without weight loss (Certad et al 2003). This finding could be described that in patients with considerable weight loss the HIV disease is more severe and defect of the immune system may involve the production of eosinophils (Arora and Arora 2009). Celiac was not confirmed in our patient, however celiac disease is one of the most frequent causes of malabsorption as reported previously (Behera et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Isospora is worldwide distributed particularly in the tropical and subtropical regions (Arora and Arora 2009;Gupta et al 2008). Very limited information is available on isosporiasis infection from Iran, few cases were reported in a recent study of 356 HIV-positive patients (Agholi et al 2013) and as a case report (Hazrati Tappeh et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonly reported parasites include Cryptosporidium parvum, Isospora belli, Microsporidium spp, Giardia lamblia, Entamoeba *Address correspondence to this author at the Department of Microbiology, Faculty of Science, Ahmadu Bello University, Zaria-Nigeria; Tel: +234 803 328 7031; E-mail: maryamaminu@yahoo.com histolytica and Cyclospora spp. [4]. Cryptosporidium, Cyclospora and Isospora have been shown to complicate HIV infection by causing chronic diarrhoea which facilitates progression to AIDS [5][6][7][8][9][10].…”
Section: Human Immunodeficiency Virus (Hiv) Infection Is a Global Heamentioning
confidence: 99%
“…However, all organisms do not represent an equal threat [1]. Most of these patients die of infections other than HIV [2]. The gastrointestinal tract is the major surface where contact between man and environment takes place.…”
Section: Introductionmentioning
confidence: 99%